2016
DOI: 10.3415/vcot-15-07-0115
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of pin and tension-band wire fixation with a prototype locking plate fixation in a transverse canine patellar fracture model

Abstract: The failure mode with pin/TBW was consistently similar to failures observed clinically. The LP demonstrated consistent, reliable and stable fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(76 reference statements)
0
8
0
1
Order By: Relevance
“…Group D was found to have two mechanisms of failure. Initially elongation of the tension band wire loop was noted in both testing modes, but this was accompanied by either sliding of the pin distally through the proximal fragment as the inter-fragmentary gap increased, or by the pin cutting through the bone proximally or distally as previously noted (25). It is possible that had thicker wire been utilised then resistance to elongation and reduced gap opening would have been observed.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Group D was found to have two mechanisms of failure. Initially elongation of the tension band wire loop was noted in both testing modes, but this was accompanied by either sliding of the pin distally through the proximal fragment as the inter-fragmentary gap increased, or by the pin cutting through the bone proximally or distally as previously noted (25). It is possible that had thicker wire been utilised then resistance to elongation and reduced gap opening would have been observed.…”
Section: Discussionmentioning
confidence: 79%
“…Only one biomechanical study of patellar fractures has been published in the peer reviewed veterinary literature (25). This study compared the use of a prototype locking plate with pin and tension band wire and concluded that pin and tension band wiring was an unsuitable method in the dog.…”
Section: Introductionmentioning
confidence: 99%
“…3 Due to the paucity of literature on canine patellar fracture, most of the described fracture repair methods are extrapo-lated from human biomechanical and clinical studies which include several forms of tension band apparatus fixation, [4][5][6][7][8][9] cerclage wire fixation 3 and plate fixation. 6,[10][11][12][13][14][15] Pin and tension band wire (TBW) approaches have long been the recommended treatment for patellar fracture repair in both veterinary and human patients. [3][4][5] The use of a TBW is theorized to counteract the tensile force created by muscular contraction and convert it into a compressive force, resulting in interfragmentary compression and fracture stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several technical modifications, management of patellar fractures by different types of plate fixation has been reported. [4][5][6][7] Operative management of comminuted patella fractures continues to be a challenge with poor functional outcomes and high reoperation rates.…”
Section: Introductionmentioning
confidence: 99%